Hydrazine Complexes of Lanthanides with 3-Acetoxy- and 4-Acetoxybenzoic Acids: Spectroscopic, Thermal, and XRD Studies - E. Helen Pricilla Bai; S. Vairam (Journal of Chemistry)
New bis-hydrazine lanthanide complexes with 3-acetoxybenzoic acid (3-abH) of formula, [Ln(3-ab)3(N2H4)2]·xH2O where Ln = La, Ce, Pr and Gd and x=0; Ln = Nd  and  Sm and x=1, and monohydrazine complexes of some trivalent lanthanides with 4-acetoxybenzoic acid (4-abH) of formula, [Ln(4-ab)3(N2H4)]·H2O where Ln = La, Ce, Pr, Nd, Sm and Gd have been prepared in ethanolic medium and characterized by spectroscopic techniques (IR and UV reflectance), microelemental analysis, thermoanalytical technique, powder XRD, SEM-EDS studies, and magnetic susceptibility measurements. The IR spectra of both series show bidental coordination of carboxylate ion with the metal by displaying, νC=O (asym) in the range of 1587–1602 cm−1 and the νC=O (sym) in the range of 1433–1410 cm−1, with a separation of around 200 cm−1. The ester C = O remains unaltered indicating the noninvolvement in coordination. All the complexes show νN-N absorption in the range of 929–962 cm−1 indicating the presence of hydrazine in a bridged bidentate fashion. The thermal data reveals that the hydrated compounds show endothermic dehydration followed by exothermic decomposition to leave their metal oxide as end products, and the anhydrous compounds undergo exothermic decomposition to form the respective metal oxide residues.